Teacher’s Target Language Use in Classroom Discourse: Teacher’s Point of View - Puspa Sari; Syahrir Syahrir; Husnani Aliah (EDUPEDIA, 2021)
The language class is closely related to the assumption that students will learn and generate the target language. Students are supposed to be able to relate, at least, with the language they have studied. The teacher hopes to not only teach but also use the target language in their teaching-learning process and show the students how to use it. This research explores the teacher's target language in the classroom discourse from the teacher’s point of view—a Qualitative approach employed in this research. The teacher believed that the use of the target language has to be in a maximum way. However, drawn away by the situation of students’ target language knowledge, the use of target language becomes infrequently used. She only used target language for simple words or sentences, which is she knew her students able to comprehend. She needed to use the target language and the students’ first language and mother tongue to help the students more comfortable comprehending the lesson.